Unified legal regulation of bank interest and commissions - A comparative study between Islamic law and law – - Al-Baydani, Haitham Ismail Muhammad (Journal of Economic, Administrative and Legal Sciences, 2023)
Numerous rulings, rules and controls are drawn from the Qur’anic verses, in addition to the clear and explicit verses indicating the prohibition of usury. Banks do not consider their work as lending and borrowing only, but this must be corrected, detailed and classified in several areas: the first in the field of economics and investment in accordance with the system derived from the provisions of religion and in the field of a good loan to meet people’s needs and not exploit that and development with legitimate projects and businesses, and the main objective of the research is to unify a legal system derived from The provisions of the Islamic religion with its purposes and rules and avoiding dealing with Western interest systems and following the analytical and comparative approach. He talked about the concept of system and organization, and mentioned some fundamental and jurisprudential rules and legal controls on contracts and banking transactions, and the legal and legal nature of interest and bank currencies, are they prohibited or not, and mentioned similarities and differences between Sharia And the law, and a brief mention of the extent to which interest is dealt or not in banks on the contemporary reality of some countries, including Yemen. And he reached several results, the most important of which are: Most banks do not free their transactions and banking operations from quasi-usury and forbidden usury. Islamic banks have been licensed by the central bank in the country, which deals in its operations and banking transactions with usurious interest, the discrepancy and contradiction of fatwas, whether issued by the Sharia bodies of Islamic banks or issued by the same Sharia body of the Islamic bank in similar banking transactions and operations. The Islamic Development Bank did not strictly implement the provisions of Islam, and its submission to the modern American banking system. The most important recommendations: It is necessary to follow the religion of monotheism, and the necessity of unifying a legal system that controls, restricts, and shows correct transactions free from any illicit or usurious suspicions in banking operations, and restructuring banks.
Keywords: Banking interests and commissions; controls and rules; usury; deposit and loan; contemporary reality of banks